Impact of alcoholic extract of Morus alba leaves on the in vitro crystallization of calcium oxalate - Kolekar, Ankita M.; Gaikwad, D. K. (Journal of Neonatal Surgery, 2025)
The in vitro analysis of nucleation and aggregation assays to evaluate the antiurolithiatic efficacy of Morus alba was carried out. The ethanolic extracts of M. alba shown antioxidant potential with DPPH radicals Scavenging activity with, increasing concentrations. The GCMS/MS, FT-IR and HRLC-MS/MS profiling of M. alba extracts indicates the presence of phytoconstituents and secondary bioactive compounds, which improves the aggregation and nucleation inhibition of calcium oxalate crystals. The extracts of M. alba leaves possessing significant nucleation and aggregation properties, may be utilized in the formulation of herbal medications for kidney stones.